2004
DOI: 10.1289/ehp.6601
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopment and Endocrine Disruption

Abstract: In this article I explore the possibility that contaminants contribute to the increasing prevalence of attention deficit hyperactivity disorder, autism, and associated neurodevelopmental and behavioral problems in developed countries. I discuss the exquisite sensitivity of the embryo and fetus to thyroid disturbance and provide evidence of human in utero exposure to contaminants that can interfere with the thyroid. Because it may never be possible to link prenatal exposure to a specific chemical with neurodeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
134
1
3

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(140 citation statements)
references
References 50 publications
2
134
1
3
Order By: Relevance
“…Chemical exposure was considered one candidate etiology (12)(13)(14), however, the present study revealed no statistically significant association between PCBs concentration in preserved umbilical cords and autism. Firm conclusions cannot be drawn from the present results as to whether in utero PCBs exposure is not one of the etiologies of autism because of the small sample size as well as the external contamination of preserved umbilical cord samples used as an indicator of in utero exposure to PCBs.…”
Section: Resultscontrasting
confidence: 78%
See 1 more Smart Citation
“…Chemical exposure was considered one candidate etiology (12)(13)(14), however, the present study revealed no statistically significant association between PCBs concentration in preserved umbilical cords and autism. Firm conclusions cannot be drawn from the present results as to whether in utero PCBs exposure is not one of the etiologies of autism because of the small sample size as well as the external contamination of preserved umbilical cord samples used as an indicator of in utero exposure to PCBs.…”
Section: Resultscontrasting
confidence: 78%
“…We applied our proposed in utero exposure assessment method to autistic patients to determine whether there is any relationship between autism and in utero PCBs exposure. Chemical exposure is suspected as one of the etiologies of autism (12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies on endocrine disruption and NRs have discussed reproductive effects and effects on the immune and nervous systems, and several excellent reviews are available on these topics (Singleton & Khan 2003, Colborn 2004, Panzica et al 2005, Vidaeff & Sever 2005, Tabb & Blumberg 2006. We focus here on the possible involvement of EDCs in the development of obesity and metabolic syndrome (MetS).…”
Section: Is Exposure To Edcs Involved In Development Of Metabolic Dismentioning
confidence: 99%
“…It prepared scientists to entertain the possibility that endocrine-disrupting environmental chemicals could also interfere with developmental processes. Many publications have explored these implications (e.g., Colborn, 2004;Schantz and Widholm, 2001;Weiss, 2002a;Melcagni and Panzica, 2006). The effects of these chemicals on aging, in contrast, are a tabula rasa.…”
Section: Endocrine Disruptorsmentioning
confidence: 99%